Effects of Leading Edge Sweep on the Cavitating Characteristics of Inducer Pumps - Allan J. Acosta; Yoshinobu Tsujimoto; Yoshiki Yoshida; Seiji Azuma; Paul Cooper (International Journal of Rotating Machinery)
It is well known that leading edge sweep has a favorable effect on the cavitation of turbomachines. However, the mechanisms of the improvement have not been made clear. It has been shown that the lift and the drag on a cavitating swept single hydrofoil can be correlated fairly well based on the velocity component normal to the leading edge. In the present paper, such correlations for swept cascades are derived and the results are examined, neglecting the full geometrical effects of the inducer rotor. It is shown that the correlations can simulate the developments of various types of cavitation, including alternate blade cavitation, rotating cavitation, and cavitation surge. This result is based on the observation that the steady cavity length, as well as the developments ofvarious types ofcavitation, is fairly well predicted by the correlation.